Building relationships with remote participants through playful technology interactions in online codesign - Paay, Jeni; Taffe, Simone; Pedell, Sonja (Design and Technology Education: An International Journal, 2023)
“Hybrid is here to stay!” If that is so, then how we educate design students and the techniques they learn need to work in a technology-driven online environment as well as face-to-face on campus. Learning codesign typically involves students being in a design studio environment where they create activities using tangible materials, for use in workshops, giving participants hands-on experiences to gather useful design insights. The question is, how does codesign need to be adapted to be effective in an online environment? To identify those elements of codesign that work effectively online, we offer lessons learned from teaching codesign online during the lockdowns and the resulting isolation of academics and students imposed by the COVID-19 pandemic. This necessitated rapidly adapting on-campus codesign techniques to online versions using available technologies to engage remote participants in online participatory experiences. We describe codesign activities of design teams who created 24 unique online activities to explore designs for Welcoming Community onto Campus, trialling them in virtual workshops with the local community. Case study method was used to collect and analyse weekly student reflections and educator observations using thematic analysis and basic inductive coding. The unexpected finding is that online codesign activities need to remain tactile and include multisensory qualities. We argue that online codesign needs to focus on building relationships, engaging the senses, keeping it simple and allowing flexible timing. We identify the benefits, challenges and implications for online codesign and provide a checklist for designers wanting to prepare for a hybrid codesign future.